Campus sustainability research: indicators and dimensions to consider for the design and assessment of a sustainable campus - Ayotunde Dawodu; Haoyue Dai; Tong Zou; Hongjie Zhou; Wenhan Lian; Jumoke Oladejo; Felix Osebor (Heliyon, 2022)
Assessment Tools have become the de facto method to address sustainability issues within the built environment. They provide a measurable third-party approach to ensuring sustainability design and directives are met through the use of indictors, criteria’s and credit system. A key challenge is that the existing tools such as BREEAM Communities and LEED Neighbourhood Development address a wider community but cannot efficiently address the more nuanced and context specific sustainability requirements of campuses. However, the approach of utilizing credits, indicator and criteria systems is a tactic that campus planners have slowly began to imbibe. This is even more critical to sustainable development cities due to the huge amounts of land and human resources consumed on campuses; However, gaps exist within the currently existing Campus Sustainability Assessment Tools (CSAT) that have been developed. Generally. Though studies have identified trends and gaps in neighbourhood and building assessment tools, no comprehensive study has investigated the potential gaps from the newly emerging CSATs. Using bibliometric analysis, this study reviews over 1000 articles on campus sustainability and assessment tools with the aim of determining the gaps, trends and focus area of campus sustainability via CSAT. The result draw out 15 dimensions that govern the design of sustainable campuses, and the most predominant dimensions were environmental, educational and governance dimension. The results also highlight the importance of context in implementing and developing CSATs and showed numerous overlooked campus sustainability issues, which have considerable impact on the determining the claims that makes campuses sustainable. Finally, results demonstrated a need to enhance inclusivity in decision making on campus via different survey techniques in both education and implementation of campus sustainability initiatives. In sum this study enhances the development of new CSAT and campus sustainability initiative and the modification existing initiatives to effectively meet the required sustainability standards within the built environment.